A biomimetic 3D airflow sensor made of an array of two piezoelectric metal-core fibers. Issue 3 (19th June 2017) - Bian, Yixiang; He, Can; Sun, Kaixuan; Dai, Longchao; Shen, Hui; Jin, Hong; Gong, Junjie
Abstract : Purpose: The purpose of this paper is to design and fabricate a three-dimensional (3D) bionic airflow sensing array made of two multi-electrode piezoelectric metal-core fibers (MPMFs), inspired by the structure of a cricket's highly sensitive airflow receptor (consisting of two cerci). Design/methodology/approach: A metal core was positioned at the center of an MPMF and surrounded by a hollow piezoceramic cylinder. Four thin metal films were spray-coated symmetrically on the surface of the fiber that could be used as two pairs of sensor electrodes. Findings: In 3D space, four output signals of the two MPMFs arrays can form three "8"-shaped spheres. Similarly, the sensing signals for the same airflow are located on a spherical surface. Originality/value: Two MPMF arrays are sufficient to detect the speed and direction of airflow in all three dimensions.